2002
DOI: 10.3130/aijs.67.129_4
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Seismic Earth Pressure Acting on Embedded Footing and Inertial Force Based on Liquefaction Test Using Large Scale Shear Box

Abstract: Large−scale shaking table tests are conducted to investigate phase difference between the inertial fbrce of the super − structure and total earth pressure acting on the f()oting . It is shewn that (1) The total earth pressure before liquefaction tends to be out ofphase by 180 degrees with the inertial force , (2)The total garth pressure after liquefaction tends to be in phase with 山 e inertial force , (3)Phase difference between the inertial fbrce and total earth pressure can be esti − mated by considering the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Shaking table tests using a polyacrylamide and bentonite soil model (Iiba et al, 2003) showed that the lateral response of an embedded footing is very eŠective in reducing pile stress. In contrast, Tamura et al (2002) reported that the lateral response of an embedded footing tends to increase pile stress in liqueˆed sand based on large-scale shaking table tests. These reports indicate that the evaluation of lateral response of an embedded footing is important for the seismic design of pile foundations in conformity with their performance.…”
Section: Introductionmentioning
confidence: 99%
“…Shaking table tests using a polyacrylamide and bentonite soil model (Iiba et al, 2003) showed that the lateral response of an embedded footing is very eŠective in reducing pile stress. In contrast, Tamura et al (2002) reported that the lateral response of an embedded footing tends to increase pile stress in liqueˆed sand based on large-scale shaking table tests. These reports indicate that the evaluation of lateral response of an embedded footing is important for the seismic design of pile foundations in conformity with their performance.…”
Section: Introductionmentioning
confidence: 99%
“…For building structures with embedded foundations, embedded walls have been recognized to resist horizontal loads except in cases where liquefaction occurs in the surrounding soils (e.g., Building Center of Japan, 1995; Tamura et al, 2002). The horizontal resistance of embedded foundations is influenced by several factors, including passive resistance, side friction, and base friction.…”
Section: Introductionmentioning
confidence: 99%